Integration of Transcriptomic and Metabolomic Data to Compare the Hepatotoxicity of Neonatal and Adult Mice Exposed to Aristolochic Acid I - Fang, Zhi-e; Wang, Chunyu; Niu, Ming; Liu, Tingting; Ren, Lutong; Li, Qiang; Li, Zhiyong; Wei, Ziying; Lin, Li; Mu, Wenqing; Gao, Yuan; Xiao, Xiaohe; et al. (Frontiers in Genetics, 2022)
Aristolochic acid (AA) is a group of structurally related compounds what have been used to treat various diseases in recent decades. Aristolochic acid I (AAI), an important ingredient, has been associated with tumorigenesis. Recently, some studies indicated that AAI could induce liver injury in mice of different ages, but comprehensive mechanisms of AAI-induced differences in liver injury in various age groups have not yet been elucidated. This study aims to evaluate the causal relationship between AAI-induced liver injury and age based on neonatal mice and adult mice. A survival experiment indicated that all neonatal mice survived. Moreover, the adult mice in the high-dose AAI group all died, whereas half of the adult mice in the low-dose AAI group died. In observation experiments, AAI induced more severe liver injury in neonatal mice than in adult mice under long-term than short-term exposure. Furthermore, integrated metabolomics and transcriptomics indicated that AAI disturbing steroid hormone biosynthesis, arachidonic acid metabolism, the drug metabolism-cytochrome P450 pathway and glycerophospholipid metabolism induced neonatal mice liver injury. The important role of age in AAI-induced liver injury was illustrated in our study. This study also lays a solid foundation for scientific supervision of AA safety.